2021
DOI: 10.3389/fnagi.2021.722830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fear of Falling on Mobility Measured During Lab and Daily Activity Assessments in Parkinson’s Disease

Abstract: In chronic disorders such as Parkinson’s disease (PD), fear of falling (FOF) is associated with falls and reduced quality of life. With inertial measurement units (IMUs) and dedicated algorithms, different aspects of mobility can be obtained during supervised tests in the lab and also during daily activities. To our best knowledge, the effect of FOF on mobility has not been investigated in both of these settings simultaneously. Our goal was to evaluate the effect of FOF on the mobility of 26 patients with PD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In line with this observation, studies in PD patients found an association between self-rated walking disability and FOF, but not between gait speed and FOF ( 32 , 33 ). Additionally, a study in patients with PD found a significant difference in the time needed to perform the two turns during the Timed-up-go (TUG) including the stand-to-sit movement test between individuals with and without FOF, but not in the gait speed ( 38 ). Therefore, concerning FOF, this study also highlights the importance of the capability to perform transitions and does not see gait speed per se as relevantly predictive of this symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this observation, studies in PD patients found an association between self-rated walking disability and FOF, but not between gait speed and FOF ( 32 , 33 ). Additionally, a study in patients with PD found a significant difference in the time needed to perform the two turns during the Timed-up-go (TUG) including the stand-to-sit movement test between individuals with and without FOF, but not in the gait speed ( 38 ). Therefore, concerning FOF, this study also highlights the importance of the capability to perform transitions and does not see gait speed per se as relevantly predictive of this symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the importance of balance with regard to FOF, an intervention study was able to show that balance training reduces FOF in older institutionalized patients (37). Evidence on the relationship between FOF and gait speed (which is represented by walking duration in the SPPB) differs in the literature (32,(38)(39)(40)(41). For example, a study in patients with PD found a correlation between FOF and gait speed in bivariate analysis, but not in multivariate regression analysis (32).…”
Section: Introductionmentioning
confidence: 99%
“…FOF restricts mobility, social participation, and quality of life [ 5 , 6 ]. FOF predicts future falls and therefore is relevant to consider FOF for fall risk assessment [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear of falling (FOF) is a common and serious problem in patients with PD, which influences gait patterns [16,17]. FOF has been defined as ongoing concern about falling, low fall-related self-efficacy, and activity avoidance [18].…”
Section: Introductionmentioning
confidence: 99%